Leaf-transcriptome profiles of phoebe bournei provide insights into temporal drought stress responses - Li, Xiang; Liu, Lanlan; Sun, Shixian; Li, Yanmei; Jia, Lu; Ye, Shili; Yu, Yanxuan; Dossa, Komivi; Luan, Yunpeng (Frontiers in Plant Science, 2022)
Phoebe bournei (Hemsl.) Yang is used as a commercial wood in China and is enlisted as a near-threatened species. Prolonged droughts pose a serious threat to young seedlings (1-2 years old). A transcriptome sequencing approach, together with the measurement of growth parameters and biochemical analyses were used to understand P. bournei’s drought responses on 15d, 30d, and 45d of drought stress treatment. The stem and root dry weights decreased significantly with drought stress duration. Activities of antioxidative enzymes i.e., peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT) increased significantly with the increase in drought stress duration. A total of 13,274, 15,648, and 9,949 genes were differentially expressed in CKvs15d, CKvs30d, and CKvs45d, respectively. The differential expression analyses showed that PSI and PSII underwent structural changes, chlorophyll biosynthesis, and photosynthesis were reduced. The genes annotated as POD, SOD, and CAT were upregulated in drought-treated leaves as compared to control. Additionally, plant-hormone signal transduction, MAPK signaling-plant, phenylpropanoid biosynthesis, flavonoid biosynthesis, and starch and sucrose metabolism pathways showed large-scale expression changes in major genes. We also found that members of 25 transcription factor families were differentially expressed. Our study presents and discusses these transcriptome signatures. Overall, our findings represent key data for breeding towards drought stress tolerance in P. bournei.